Personality Type Of Efl Learners On Reading Comprehension At Smp N 2 Tapian Dolok - Dona Atalatha Samosir; Dumaris E Silalahi; Tiarma I Marpaung (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aim to investigate the personality type of EFL learners on reading comprehension at SMP N 2 Tapian Dolok. This research method is design as qualitative. The sample of research is taken from IX-2 class that consist of 9 to purposively. The characteristics of the sample are three learners with the highest average scores, three learners with middle average scores, and three learners with the lowest average score. The technique collecting data is interview. The researcher gives some question to the learners and the total questions of question are eight question. The questions are related to the personality type in reading comprehension. The result of this research showed that personality types of learners are different. The researcher found extroverted personality is less often than introverted personality.. From the nine learners, 3 learners are extroverted Personality and 6 learners are introverted personality. The learners with extrovert personality type get higher score on reading comprehension than introvert personality type.